High Y‐chromosomal Differentiation Among Ethnic Groups of Dir and Swat Districts, Pakistan. (3rd August 2017) - Ullah, Inam; Olofsson, Jill K.; Margaryan, Ashot; Ilardo, Melissa; Ahmad, Habib; Sikora, Martin; Hansen, Anders J.; Shahid Nadeem, Muhammad; Fazal, Numan; Ali, Murad; Buchard, Anders; Hemphill, Brian E.; et al.
Summary: The ethnic groups that inhabit the mountainous Dir and Swat districts of northern Pakistan are marked by high levels of cultural and phenotypic diversity. To obtain knowledge of the extent of genetic diversity in this region, we investigated Y‐chromosomal diversity in five population samples representing the three main ethnic groups residing within these districts, including Gujars, Pashtuns and Kohistanis. A total of 27 Y‐chromosomal short tandem repeats (Y‐STRs) and 331 Y‐chromosomal single nucleotide polymorphisms (Y‐SNPs) were investigated. In the Y‐STRs, we observed very high and significant levels of genetic differentiation in nine of the 10 pairwise between‐group comparisons ( R ST 0.179–0.746), and the differences were mirrored in the Y‐SNP haplogroup frequency distribution. No genetic differences were found between the two Pashtun subethnic groups Tarklanis and Yusafzais ( R ST = 0.000). Utmankhels, also considered Pashtuns culturally, were not closely related to any of the other population samples ( R ST 0.451–0.746). Thus, our findings provide examples of both associations and dissociations between cultural and genetic legacies. When analyzed within a larger continental‐scale context, these five ethnic groups fall mostly outside the previously characterized Y‐chromosomal gene pools of the Indo‐Pakistani subcontinent. Male founder effects, coupled with culturally and topographically based constraints upon marriage and movement, are likely responsible for the high degree of genetic structure in this region.